2002
DOI: 10.1007/s00247-001-0603-5
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular myxoma: a rare neck mass in a child

Abstract: Intramuscular myxoma (IM) is a true mesenchymal benign tumour which is rare in both adults and children. In children, it most commonly affects the heart, mandible or maxilla. We report a 5-year-old child with IM presenting as a posterolateral neck mass and review the literature. IM, although very rare, should be included in the differential diagnosis of neck masses in the paediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…In the case described, the evolution of the pain was 5 years and the patient noted an enlarging mass over 1 year. In the cases of IM in the cervical paraspinal muscles reported by Shugar et al [17.] and Crankson et al [5], the clinical manifestation was a gradually enlarging non-painful mass in the posterior cervical region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case described, the evolution of the pain was 5 years and the patient noted an enlarging mass over 1 year. In the cases of IM in the cervical paraspinal muscles reported by Shugar et al [17.] and Crankson et al [5], the clinical manifestation was a gradually enlarging non-painful mass in the posterior cervical region.…”
Section: Discussionmentioning
confidence: 99%
“…CT typically reveals a cystic-looking mass, as was this case, with an attenuation value greater than water, but less than surrounding normal muscle and no enhancement after intravenous administration of contrast medium [5,8,9]. On MRI, IM have sharp borders with homogeneous low-signal intensity, lower than skeletal muscle, on T1-weighted images and homogenous high intensity, brighter than fat, on T2-weighted images [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Pahor and Samant (1994) found only 60 cases of soft tissue myxomas of the head and neck reported in the literature. 4 Since that study, there have been only 19 additional cases reported to date [5][6][7][8][9][10][11][12][13][14][15][16] (Table 1). In their study, Pahor and Samant presented the first case of a retropharyngeal soft tissue myxoma managed with a transcervical approach for resection.…”
mentioning
confidence: 99%